2008
DOI: 10.1177/0886260508317190
|View full text |Cite
|
Sign up to set email alerts
|

The Prosecution of Hate Crimes

Abstract: Since the development of bias crime legislation over the past few decades, scholars have debated the merits of the legislation and questioned its enforcement.(1) In light of such concerns, this study presents characteristics of all cases prosecuted as bias crimes in a New Jersey county between 2001 and 2004 and applies the hate crime typology originally developed in 1993. Results show that, in this jurisdiction, the typology is an inadequate tool for classifying cases prosecuted as hate crimes. Approximately o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The Miami‐Dade State Attorney's Office provided access to case files for criminal cases processed as hate crimes in Miami for the period 2005–2019. There were 23 hate crime cases during this time, which included those motivated by victims' race, religion, sexual orientation, mental disability, or homelessness (a comparable number of cases was reviewed by Phillips, 2009 when studying hate crimes in New Jersey). Cases involving juveniles are sealed and not available for review.…”
Section: Datamentioning
confidence: 99%
“…The Miami‐Dade State Attorney's Office provided access to case files for criminal cases processed as hate crimes in Miami for the period 2005–2019. There were 23 hate crime cases during this time, which included those motivated by victims' race, religion, sexual orientation, mental disability, or homelessness (a comparable number of cases was reviewed by Phillips, 2009 when studying hate crimes in New Jersey). Cases involving juveniles are sealed and not available for review.…”
Section: Datamentioning
confidence: 99%
“…Although frequently seen as the most prototypical bias crime offender, those who were motivated to do harm because of deeply held racist, misogynist, heterosexist, or other privileged beliefs were the least common type of bias crime offender. Others have attempted to characterize other specific types of bias crime, such as online hate crimes (Jacks & Adler, 2015), or hate against Muslims on social media (Awan, 2014), though none have been expansive as Levin and McDevitt's typology. While widely cited, a later critique of Levin's and McDevitt's typology that attempted to replicate the findings highlight that roughly a third of cases that do not fit neatly into these four categories (Phillips, 2009), and that additional categories may be necessary (Pezzella, 2017), suggesting that there is still more to learn about bias crime offenders. Rather than separating bias crime types into a typology, some scholars have proposed underlying mechanisms for what may be driving bias crimes overall.…”
Section: Characteristics Of Bias Crimes and Bias Crime Perpetratorsmentioning
confidence: 99%
“…The crimes they committed seemed to be the result of group pressure coupled with the use alcohol [34:202-203, 59]. Other studies suggest a prevalence of mental illness among seemingly ideologically inspired offenders [52]. However, in our survey it emerged that ideological offenders of bias speech are significantly less often under the influence of alcohol: only 17% of malignant bias offenders was under influence while committing the bias speech, compared to 45% of the offenders in the other categories (N0198; p<0.05).…”
Section: Net-widening In Cases Of Malignant or Ideological Motivesmentioning
confidence: 99%
“…The European Union (EU) 2008 Framework Decision on combating certain forms and expressions of racism and xenophobia and the Council of Europe (CoE) 2002 Recommendation on national legislation to combat racism and racial discrimination both recommend more severe punishment for offences that are committed with a 'racist or xenophobic motivation' [14,18]. 1 However, it has been observed that such penalty enhancement is frequently applied to offences that are not motivated by bias [20,30,52]. Then, the penalty enhancement loses its justification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation